Effects of the addition of exogenous lipase on lipolysis and lipid oxidation during wet‐curing and dry‐ripening of silver carp inoculated with mixed starter cultures. (30th July 2021) - Wang, Caixia; Sang, Shengwang; Qian, Dengfan; Jian, Yuying; He, Xin; Li, Xiyuan; Li, Cheng; Liu, Yuntao; Chen, Saiyan
Summary: Lipid degradation caused by lipolysis and oxidation plays an important role in the evolution of final product quality of cured silver carp. This study aimed to determine the impact of exogenous lipase (ExL) on lipolysis and lipid oxidation during the wet‐curing and dry‐ripening of silver carp inoculated with mixed starter cultures. The addition of ExL to silver carp increased the hydrolysis of total lipids and phospholipids. The free fatty acids (FFAs) content during wet‐curing was significantly higher in the ExL‐treated group compared with the control. Increased FFA accumulation contributed to a high level of conjugated dienes, peroxides and thiobarbituric acid‐reactive substances in the ExL‐treated group, indicating that the lipid oxidation was improved by the addition of ExL. Increased neutral lipase, acid lipase and phospholipase activities during the wet‐curing stage might explain the more extensive release of FFAs in the presence of ExL. The addition of ExL promotes the hydrolysis and oxidation of lipids in cured silver carp. Abstract : Exogenous lipase enhances the accumulation of free fatty acids and elevates the level of lipid oxidation in cured silver carp.